Discontinuous hyperpolarization schemes in liquid-state overhauser dynamic nuclear polarization experiments - Alex van der Ham (Journal of Magnetic Resonance Open)
Liquid-state Overhauser Dynamic Nuclear Polarization (ODNP) is an emerging technique, aimed at shortening NMR experiment times. It achieves this by increasing the otherwise poor nuclear polarization at room temperature, by polarization transfer from excited electron spins. The present work explores two ideas, aimed at achieving the optimal signal-to-noise per time unit for a given system, and quantitation of spectra showing a large disparity in ODNP enhancements at high magnetic fields (≥ 9.4 T). Both of these ideas are predicated on, perhaps counterintuitively, not allowing full dynamic nuclear polarization to build up, either by rapid rf pulsing, or gating of the microwave irradiation.